An Integrated In Silico and In Vitro Assays of Dipeptidyl Peptidase-4 and α-Glucosidase Inhibition by Stellasterol from Ganoderma australe - Krisyanti Budipramana; Junaidin Junaidin; Komar Ruslan Wirasutisna; Yanatra Budi Pramana; Sukrasno Sukrasno (MDPI AG, 2019)
Background: Ganoderma fungus is rich in terpenoids. These compounds are known for their anti-hyperglycemic activities. However, the study of terpenoids as the secondary metabolite from Ganoderma as a dipeptidyl peptidase-4 (DPP-4) inhibitor remains unexplored. In addition, we examined the α-glucosidase inhibition activity. Objective: This study aimed to isolate the major terpenoid from non-laccate Ganoderma and examined its inhibitor activity on DPP-4 and α-glucosidase enzymes, and its interaction. Methods: The compound was isolated using column chromatography from Ganoderma australe. The structure of the isolated compound was confirmed by 1H and 13C nuclear magnetic resonance spectroscopy, while the inhibitory activity was evaluated using an enzymatic assay. The interaction of the isolated compound with DPP-4 and α-glucosidase enzymes was investigated using an in silico study. Results: The isolated compound was identified as stellasterol; IC50 values for DPP-4 and α-glucosidase inhibitor were 427.39 µM and 314.54 µM, respectively. This study revealed that the inhibitory effect of stellasterol on DPP-4 enzyme is through hydrophobic interaction, while the α-glucosidase enzyme is due to the interaction with six amino acids of the enzyme. Conclusion: Stellasterol is the major component of the steroid from G. australe. Enzyme inhibitory assay and in silico study suggest that stellasterol may contribute antidiabetic activity with a mechanism closer to acarbose rather than to sitagliptin.